FINANCIAL ACCESS, FINTECH ADOPTION, AND THEIR IMPACT ON SME SURVIVAL: EVIDENCE FROM CONTEMPORARY FINANCE LITERATURE - Erviani Anggie Kharerina (Resilience of Small Medium Business, 2025)
Objective: This study aims to synthesize contemporary financial literature to examine how access to finance and the adoption of financial technology (fintech) jointly affect the sustainability of micro, small, and medium enterprises (MSMEs), particularly in the context of economic uncertainty and global crisis. Research Design & Methods: This study uses a systematic literature review approach based on the Scopus database with bibliometric analysis and thematic synthesis. A total of 77 relevant scientific articles were analyzed through publication trend mapping, keyword co-occurrence networks, and thematic grouping to identify patterns, mechanisms, and conceptual relationships between financial access, fintech adoption, and MSME resilience. Findings: The synthesis results show that access to external financing, particularly through bank credit, working capital, and risk-sharing financing mechanisms, remains a key determinant of MSME survival. However, post-2020 literature emphasizes that fintech adoption serves as a strategic complement that increases the speed of liquidity access, reduces transaction costs, and expands financial inclusion. The integration of traditional and digital financing has proven to be more effective in improving MSME resilience than reliance on a single source of financing. Implications & Recommendations: These findings indicate the need to strengthen a hybrid financing ecosystem that integrates banking and fintech to support SME sustainability. Policymakers are advised to promote adaptive and inclusive fintech regulations, while financial institutions need to develop collaborative financing models that are responsive to SME needs in both crisis and non-crisis conditions. Contribution & Value Added: This article contributes by synthesizing fragmented evidence and proposing a mechanism-oriented conceptual framework that specifies how access to finance and fintech adoption interact to influence MSME sustainability. By clarifying these interaction pathways, the study advances the literature on inclusive finance and MSME resilience and provides a focused analytical basis for future research and policy.